The Effect of Diuretics on Patients with Heart Failure: A Network Meta-Analysis: Diuretics Effect on Heart Failure Patients - Zhao, Xingsheng; Ren, Yu; Li, Hui; Liu, Xi (Journal of Pharmacy & Pharmaceutical Sciences, 2019)
Purpose: We aimed to comprehensively evaluate the curative effect of torasemide, tolvaptan, furosemide and azosemide on patients with heart failure. Methods: Relevant studies were retrieved by searching the electronic databases until May 2018. Quality assessment and data extraction of selected studies were evaluated by two reviewers. Heterogeneity across studies was assessed utilizing the I2 statistic and Q-test, and appropriate effect model was selected to calculate the pooled effect size. Network meta-analysis was conducted and the convergence degree of model was evaluated. Results: A total of 12 studies were enrolled in this study. Significant heterogeneity was not identified across the studies. Significantly greater differences were found in left ventricular ejection fraction (LVEF) for furosemide VS. azosemide, in brain natriuretic peptide (BNP) for furosemide VS. azosemide and furosemide VS. torasemide, and in adverse effects for furosemide VS. torasemide through Meta-analysis of direct comparison. In addition, network meta-analysis results suggested there were no significant differences in adverse effects, mortality, BNP and LVEF among these groups. However, the relatively low mortality and small improvement of BNP and LVEF were found in HF patients treated with torasemide. Conclusion: Torasemide might be an optimal treatment for HF patients considering its comprehensive curative effect.